Manufacturing method of polystyrene resin extruded foam board

The method addresses the challenge of maintaining low thermal conductivity and ensuring a good appearance in polystyrene-based resin extruded foam plates by using a specific blend of HFOs in the extrusion process, achieving effective thermal insulation and flame retardancy.

JP7674229B2Active Publication Date: 2025-05-09JSP CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021200027
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-09
Publication Date
2025-05-09
Estimated Expiration
2041-12-09

AI Technical Summary

Technical Problem

Existing methods for manufacturing polystyrene-based resin extruded foam plates struggle to maintain low thermal conductivity over a long period while ensuring a good appearance and adequate flame retardancy.

Method used

A method involving the extrusion of a foamable resin composition comprising polystyrene-based resin, a flame retardant, and a specific blend of hydrofluoroolefins (HFOs) as physical foaming agents, with a controlled ratio and amount of 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz), 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd), and 1-chloro-3,3,3-trifluoropropene (HFO-1233zd), to achieve the desired properties.

Benefits of technology

The method results in foam plates with excellent long-term low thermal conductivity, good surface smoothness, few gas spots, small shrinkage, and a superior exterior appearance, while meeting stringent flame retardancy standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007674229000001
    Figure 0007674229000001
  • Figure 0007674229000002
    Figure 0007674229000002
Patent Text Reader

Abstract

To provide a method for manufacturing a polystyrene-based resin extruded foamed plate which can suppress thermal conductivity to be low over a long period, and has good appearance.SOLUTION: A method for manufacturing a polystyrene-based resin extruded foamed plate which has apparent density of 20-50 kg / m3 and an extrusion direction vertical cross sectional area of 100 cm2 or more includes a step of extruding a foamable resin composition obtained by kneading a base material resin containing a polystyrene-based resin as a main component, a flame retardant, and a physical foaming agent, and molding the extruded resin composition into a plate shape by a molding tool, wherein the physical foaming agent contains a foaming agent A composed of 1,1,1,4,4,4-hexafluoro-2-butene, and a foaming agent B composed of 1-chloro-2,3,3,3-tetrafluoropropene and / or 1-chloro-3,3,3-trifluoropropene.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an extruded polystyrene foam board, and more particularly to a method for producing an extruded polystyrene foam board that can be suitably used as an insulating material for the walls, floors, roofs, etc. of buildings. [Background technology]

[0002] Polystyrene resin extruded foam boards (hereinafter, simply referred to as "foam boards") are widely used as building insulation materials due to their excellent thermal insulation properties and mechanical strength. Such foam boards are generally produced by heating and melting polystyrene resin in an extruder, then injecting a physical foaming agent into the resulting molten material, kneading the resulting foamable molten resin mixture, and extruding the mixture into a low pressure region through a flat die or the like attached to the tip of the extruder to foam it, and forming the mixture into a plate shape using a molding tool.

[0003] The typical foaming agent used in the manufacture of the foamed board is butane such as normal butane or isobutane, which has excellent foaming properties, an ozone depletion potential of 0, a small global warming potential, and excellent heat insulation properties. However, these butanes are highly flammable and remain in the foamed board for a long period of time, making it difficult to achieve a high level of flame retardancy as specified in the flammability test method of JIS A9521:2017, and therefore there is an upper limit to the amount of butane added.

[0004] In order to solve the above problems, hydrofluoroolefins (hereinafter, also simply referred to as "HFOs") such as 1,3,3,3-tetrafluoropropene and 1-chloro-3,3,3-trifluoropropene have been used as blowing agents in recent years.

[0005] As foams produced using HFO, for example, the foams disclosed in Patent Documents 1 to 4 have been proposed so far. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2010-522808 [Patent Document 2] Special Publication No. 2019-515112 [Patent Document 3] Patent Publication No. 2021-38313 [Patent Document 4] JP 2020-521009 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the above Patent Documents 1 to 4, 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) is used alone as the HFO in the blowing agent, or 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) is used in combination with another HFO (for example, 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) or 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd)).

[0008] Among the HFOs described in Patent Documents 1 to 4, HFO-1336mzz is superior in the effect of maintaining the thermal conductivity of the foam plate low for a long period of time (long-term low thermal conductivity) compared to other HFOs (HFO-1233zd, HFO-1224yd). However, when the amount of HFO-1336mzz added is increased, the foam becomes finely porous, which may lead to poor appearance and make production difficult.

[0009] On the other hand, HFOs such as HFO-1233zd and HFO-1224yd have better bubble size controllability than HFO-1336mzz, but they have lower retention within the foam and are slightly inferior in long-term low thermal conductivity, so their contribution to the effect of reducing thermal conductivity may be insufficient depending on the blending amount and blending ratio.

[0010] When a foam board is manufactured using such a plurality of HFOs, it is necessary to determine appropriate blending amounts and blending ratios in consideration of the characteristics of each HFO. However, the proposals in the above-mentioned Cited Documents 1 to 4 did not take into consideration the blending amounts and blending ratios for achieving both long-term low thermal conductivity and excellent appearance when formed into a foam board.

[0011] The present invention has been made in view of the above background, and an object of the present invention is to provide a method for producing an extruded polystyrene foam board that can maintain low thermal conductivity for a long period of time and has a good appearance. [Means for solving the problem]

[0012] According to the present invention, there is provided a method for producing an extruded polystyrene resin foam board as described below. [1] A process for producing a foamable resin composition by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and extruding the resulting composition into a plate shape using a molding tool. 3 , cross-sectional area perpendicular to extrusion direction 100cm 2 The above-mentioned method for producing an extruded polystyrene foam board comprises the steps of: The physical blowing agent is a blowing agent A consisting of 1,1,1,4,4,4-hexafluoro-2-butene; and a blowing agent B consisting of 1-chloro-2,3,3,3-tetrafluoropropene and / or 1-chloro-3,3,3-trifluoropropene; the total amount of the physical foaming agent is 1 to 1.5 mol per kg of the base resin; The amount of the foaming agent A blended is 0.2 to 0.7 mol per 1 kg of the base resin, The amount of the foaming agent B is 0.05 to 0.6 mol per kg of the base resin, the total amount of the foaming agent A and the foaming agent B is 0.6 to 1.3 mol per kg of the base resin; The ratio of the amount of foaming agent A (mol / kg) to the sum of the amount of foaming agent A (mol / kg) and the amount of foaming agent B (mol / kg) is 30 to 90% (wherein the sum of the amount of foaming agent A and the amount of foaming agent B is 100%). [2] In the method for producing an extruded polystyrene foam board according to the invention [1], the ratio of the sum of the amount (mol / kg) of the foaming agent A and the amount (mol / kg) of the foaming agent B to the total amount (mol / kg) of the physical foaming agents is more than 50% and not more than 80%. [3] The method for producing an extruded polystyrene foam board according to the invention [1] or [2], wherein the ratio of the amount of foaming agent A (mol / kg) to the total amount of foaming agent A (mol / kg) and the amount of foaming agent B (mol / kg) is 50-85% (wherein the sum of the amounts of foaming agent A and B is 100%). [4] The method for producing an extruded polystyrene resin foam board according to any one of [1] to [3] above, wherein the physical foaming agent contains one or more kinds of foaming agent C selected from the group consisting of water, carbon dioxide, dialkyl ethers having 1 to 3 carbon atoms in the alkyl chain, and aliphatic alcohols having 1 to 5 carbon atoms, and the amount of foaming agent C is 0.3 to 0.7 mol per kg of the base resin. [5] The method for producing an extruded polystyrene resin foam board according to any one of [1] to [4] above, wherein the amount of the foaming agent A is 0.4 to 0.7 mol per kg of the base resin. Effect of the Invention

[0013] According to the manufacturing method of the present invention, there is provided a method for manufacturing an extruded polystyrene resin foam board which can provide a foam board which has excellent low thermal conductivity over a long period of time, excellent surface smoothness, few gas spots, little shrinkage, and a good appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The method for producing an extruded polystyrene foam plate of the present invention will be described in detail below. The method for producing an extruded polystyrene foam board of the present invention includes a step of extruding a foamable resin composition obtained by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and forming the extruded resin composition into a board shape using a molding tool.

[0015] Specifically, a base resin consisting of a polystyrene resin and other resins added as necessary, a flame retardant, and other additives added as necessary are melted and kneaded under heating in an extruder, a foaming agent containing a specific HFO is injected into the resulting molten mixture, and further kneaded to form a foamable resin melt, which is adjusted to a temperature suitable for foaming, extruded from a high-pressure extruder to a low-pressure region through a flat die to foam, and a forming tool such as a forming device (hereinafter also referred to as a guider) or a forming roll, which are composed of two upper and lower plates of polytetrafluoroethylene resin or the like, which are installed in parallel or so as to gradually expand from the entrance to the exit direction, is arranged at the outlet of the flat die, and the extruded foam composition is molded into a plate by passing through the forming tool. Note that in the present invention, by setting the blending amount and blending ratio of a specific HFO described later within a specific range, it is possible to obtain a good extruded foam plate even if the foam plate has a large cross-sectional area by forming into a plate.

[0016] <Base resin> (Polystyrene resin) Examples of the polystyrene resin used in the production method of the present invention include polystyrene, styrene-methyl acrylate copolymers containing 50 mol% or more of styrene unit components, styrene-ethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-maleic anhydride copolymers, styrene-polyphenylene ether copolymers, styrene-acrylonitrile copolymers, styrene-methylstyrene copolymers, styrene-dimethylstyrene copolymers, styrene-ethylstyrene copolymers, and styrene-diethylstyrene copolymers. Among these, polystyrene can be preferably used. In addition to the styrene unit component, polystyrene may contain a unit component derived from a branching agent such as a polyfunctional monomer or a polyfunctional macromonomer. The content of the styrene component unit in the copolymer is preferably 60 mol% or more, more preferably 80 mol% or more, and even more preferably 90 mol% or more.

[0017] The melt viscosity of the polystyrene resin used in the production method of the present invention is preferably 500 to 3000 Pa·s, more preferably 1000 to 2500 Pa·s, and even more preferably 1500 to 2300 Pa·s, in order to provide excellent foaming and moldability. Note that in this specification, the melt viscosity is measured based on JIS K7199:1999 at a temperature of 200°C and a shear rate of 100 sec -1 The values ​​were measured under the following conditions.

[0018] The base resin may contain an amorphous polyethylene terephthalate copolymer to enhance the heat insulation of the foam board. In this case, the amorphous polyethylene terephthalate resin is preferably blended in the base resin so as to be 5% by mass or more and less than 50% by mass, more preferably 10% by mass or more and 40% by mass or less, and even more preferably 15% by mass or more and 30% by mass or less. In the amorphous polyethylene terephthalate copolymer, the heat of fusion accompanying the melting of the resin based on JIS K7122 is less than 5 J / g. The heat of fusion is measured based on the DSC curve obtained by heating to 280°C at a heating rate of 10°C per minute, keeping at this temperature for 10 minutes, cooling to 23°C at a cooling rate of 10°C per minute, and heating again to 280°C at a heating rate of 10°C per minute using a heat flux differential scanning calorimeter according to the heat flux differential scanning calorimetry method in JIS K7122 (1987).

[0019] The melt viscosity of the amorphous polyethylene terephthalate copolymer is preferably 500 to 3000 Pa·s, more preferably 1000 to 2500 Pa·s, and further preferably 1500 to 2300 Pa·s. From the viewpoint of compatibility with the polystyrene resin, the melt viscosity of the amorphous polyethylene terephthalate copolymer is preferably close to that of the polystyrene resin.

[0020] (Other polymers) The base resin may contain polymers other than the polystyrene resin and the amorphous polyethylene terephthalate copolymer within the scope of the present invention. Examples of other polymers include polyethylene resins (a mixture of one or more selected from the group consisting of ethylene homopolymers and ethylene copolymers having an ethylene unit content of 50 mol% or more), polypropylene resins (a mixture of one or more selected from the group consisting of propylene homopolymers and propylene copolymers having an ethylene unit content of 50 mol% or more), polyphenylene ether resins, and polymethyl methacrylate, as well as thermoplastic elastomers such as styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, hydrogenated styrene-butadiene-styrene block copolymers, hydrogenated styrene-isoprene-styrene block copolymers, and styrene-ethylene copolymers. These other polymers may be blended according to the purpose so as to be less than 50% by mass in the base resin, preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0021] In the manufacturing method of the present invention, a base resin mainly composed of a polystyrene-based resin means that 50% by mass or more of the base resin is a polystyrene-based resin, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0022] <Physical foaming agent> The physical blowing agent used in the present invention contains, as essential components, blowing agent A consisting of 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) and blowing agent B containing at least one of 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd) blowing agent B1 and 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) blowing agent B2.

[0023] (Foaming agent A) Among hydrofluoroolefins, the foaming agent A, 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz), has moderate solubility in polystyrene resins and excellent retention in the foam, and can produce foam boards with excellent long-term low thermal conductivity. In addition, since it is non-flammable, it can reduce the risk of ignition due to static electricity during foam board production. Furthermore, it has a low ozone depletion potential and a very small global warming potential, making it a foaming agent with a small burden on the environment. However, foaming agent A is thought to generate bubbles relatively quickly, and if added in excess, it may inhibit the smoothness of the foam board and deteriorate the appearance. This tendency is particularly noticeable when attempting to obtain a foam with a large cross-sectional area, such as a thick extruded foam board.

[0024] (Foaming agent B1) The blowing agent B1, 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd), has moderate solubility in polystyrene resins and low thermal conductivity, and also has excellent cell size controllability, making it possible to manufacture foamed boards with low apparent density. It is also non-flammable, has a low ozone depletion potential, and is an environmentally friendly blowing agent. However, the foaming agent B1 has a characteristic that it remains somewhat inferior in bubbles compared to foaming agent A and is more likely to escape from the foam board, making it difficult to maintain the thermal conductivity of the foam board at a low level for a long period of time.

[0025] (Blowing agent B2) The blowing agent B2, 1-chloro-3,3,3-trifluoropropene (HFO-1233zd), has moderate solubility in polystyrene resins and low thermal conductivity, similar to the blowing agent B1, and has excellent bubble size controllability, so that it can produce a foamed board with a low apparent density. It is also non-flammable, has a low ozone depletion potential, and is a blowing agent that puts a small burden on the environment. However, the blowing agent B2 has poorer bubble retention than the blowing agent B1, so it is prone to escaping from the foamed board, and has the characteristic that it is difficult to maintain a low thermal conductivity for a long period of time.

[0026] On the other hand, the foaming agents B1 and B2 tend to improve the foaming property more easily than the foaming agent A. One of the reasons why the foaming agents B1 and B2 improve the foaming property more easily than the foaming agent A is that the foaming agents B1 and B2 contain Cl in their molecules.

[0027] (Foaming agent C) In the present invention, the above-mentioned blowing agent A and blowing agent B are used as essential blowing agents, but it is preferable to contain, as another blowing agent, one or more kinds of blowing agent C selected from water, carbon dioxide, dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms, and aliphatic alcohols having 1 to 5 carbon atoms.

[0028] Water has a small molecular weight and high foaming efficiency, which allows the apparent density of the extruded foam insulation board to be low. In addition, water reduces the environmental load and dissipates quickly from the foam board, allowing the dimensions of the resulting foam board to be stabilized quickly.

[0029] Carbon dioxide can achieve a high expansion ratio without inhibiting the flame retardancy of the resulting extruded foam insulation board, and since it has high gas permeability to the base resin, it quickly escapes from the extruded foam insulation board, making it possible to quickly stabilize the dimensional stability, insulating performance, and flame retardancy of the foam insulation board.

[0030] Like water, dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms and aliphatic alcohols having 1 to 5 carbon atoms do not destroy the ozone layer or cause global warming, and since they quickly dissipate from the foamed board, the shape of the foamed board can be quickly stabilized. Furthermore, by using dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms and aliphatic alcohols having 1 to 5 carbon atoms, a foamed board with a lower apparent density (higher expansion ratio) can be obtained.

[0031] Examples of dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, etc. Among these, dimethyl ether is preferably used. Two or more of these can also be used in combination.

[0032] Examples of the aliphatic alcohol having 1 to 5 carbon atoms include methyl alcohol (methanol), ethyl alcohol (ethanol), n-propyl alcohol, isopropyl alcohol, butyl alcohol, sec-butyl alcohol, tert-butyl alcohol, aryl alcohol, crotyl alcohol, propargyl alcohol, n-amyl alcohol, sec-amyl alcohol, isoamyl alcohol, tert-amyl alcohol, neopentyl alcohol, 3-pentanol, 2-methyl-1-butanol, and 3-methyl-2-butanol. Among these, ethanol can be preferably used. Two or more of these can also be used in combination.

[0033] By blending the foaming agent C with the foaming agents A and B in a specific ratio, the resin is appropriately plasticized during foaming to improve the foamability, and a foamed board with a low apparent density can be obtained. When the foaming agent C is used together with the foaming agents A and B, it is preferable to use water and an aliphatic alcohol having 1 to 5 carbon atoms as the foaming agent C, since this makes it easier to obtain a foamed board with a low apparent density. The molar ratio of water to the aliphatic alcohol having 1 to 5 carbon atoms (water: aliphatic alcohol having 1 to 5 carbon atoms) is preferably 65:35 to 85:15, and more preferably 70:30 to 80:20.

[0034] <Amount of foaming agent> In the present invention, the total amount of the physical foaming agent is 1 to 1.5 mol per kg of the base resin. From the viewpoint of obtaining a foamed board having excellent appearance, low apparent density, and capable of maintaining low thermal conductivity even after a long period of time, the total amount of the physical foaming agent is preferably 1.1 to 1.4 mol, more preferably 1.2 to 1.4 mol, per kg of the base resin.

[0035] The total amount of the foaming agent A and the foaming agent B is in the range of 0.6 to 1.3 mol, and preferably in the range of 0.7 to 1.1 mol, per kg of the base resin.

[0036] Furthermore, the ratio of the sum of the blending amount (mol / kg) of foaming agent A and the blending amount (mol / kg) of foaming agent B to the total blending amount (mol / kg) of the physical foaming agents (total blending amount of foaming agent A and the blending amount of foaming agent B / total blending amount of physical foaming agents) is preferably more than 50% and not more than 80%. By making the ratio more than 50%, the thermal conductivity can be kept even lower, and by making it not more than 80%, a foamed board with good appearance can be easily obtained. From this viewpoint, the ratio of the sum of the blending amount of foaming agent A and the blending amount of foaming agent B to the total blending amount of the physical foaming agents is preferably 55 to 70% per kg of the base resin.

[0037] The amount of the foaming agent A is in the range of 0.2 to 0.7 mol per kg of base resin. By setting the amount of the foaming agent A in the above range, the thermal conductivity can be maintained low especially for a long period of time among foam boards using HFO. From this viewpoint, the amount of the foaming agent A is preferably 0.4 to 0.7 mol per kg of base resin. When the amount of the foaming agent A is large, the extruded foam board can be produced more easily by using a high-mixing extruder such as a screw or a twin screw having a large ratio of the axial length of the screw to the diameter of the screw, or a tandem extruder in which the first extruder and the second extruder are connected in series, at the connecting portion between the first extruder and the second extruder, or at the connecting portion between the second extruder and the die, as necessary.

[0038] The amount of foaming agent B is 0.05 to 0.6 mol per kg of base resin. If the amount of foaming agent B is too large, many gas spots may occur, and the surface smoothness of the resulting foamed board may decrease. From this viewpoint, the amount of foaming agent B is preferably 0.1 to 0.5 mol, more preferably 0.2 to 0.4 mol, per kg of base resin.

[0039] The amount of the foaming agent B1 is preferably 0.05 to 0.5 mol, and more preferably 0.1 to 0.4 mol, per 1 kg of the base resin. The amount of the foaming agent B2 is preferably 0.05 to 0.5 mol, and more preferably 0.1 to 0.4 mol, per 1 kg of the base resin.

[0040] The content of the blowing agent B1 in the blending amount of the blowing agent B is preferably 10 to 100 mol %. The content of the blowing agent B2 in the blending amount of the blowing agent B is preferably 10 to 100 mol %.

[0041] When the foaming agent B is composed of foaming agent B1 and foaming agent B2, the molar ratio of foaming agent B1 to foaming agent B2 (foaming agent B1:foaming agent B2) is preferably 20:80 to 80:20, more preferably 30:70 to 70:30. When the molar ratio of foaming agent B1 to foaming agent B2 satisfies the above range, it is preferable because the extruded foam plate has an excellent balance between keeping the thermal conductivity low and having an excellent appearance.

[0042] The ratio of the amount of foaming agent A (mol / kg) to the total amount of foaming agent A (mol / kg) and the amount of foaming agent B (mol / kg) is in the range of 30 to 90%, and preferably in the range of 50 to 85%. Note that the condition of the ratio of the amount of foaming agent A is when the total amount of foaming agent A and the amount of foaming agent B is 100%.

[0043] The ratio of the amount (mol / kg) of foaming agent B1 to the amount (mol / kg) of foaming agent A is preferably 0.1 to 1, and more preferably 0.1 to 0.5. When the ratio is within the above range, an extruded foam board having excellent smoothness and fewer gas spots can be obtained, which is preferable.

[0044] Furthermore, the ratio of the amount (mol / kg) of the foaming agent B2 to the amount (mol / kg) of the foaming agent A is preferably 0.1 to 1, and more preferably 0.1 to 0.5. If the ratio of the amount (mol / kg) of the foaming agent B2 to the amount (mol / kg) of the foaming agent A satisfies the above range, it is particularly preferable because the thermal conductivity can be easily maintained low.

[0045] When foaming agent B is B1, the ratio of the amount of foaming agent A to the total amount of foaming agent A and foaming agent B is preferably in the range of 65 to 85%. When the ratio of the amount of foaming agent A to the total amount of foaming agent A and foaming agent B1 satisfies the above range, an extruded foam board having excellent smoothness and fewer gas spots can be obtained, which is preferable. The above conditions for the ratio of the amount of foaming agent A are based on the assumption that the total amount of foaming agent A and foaming agent B is 100%.

[0046] Furthermore, when foaming agent B2 is used as foaming agent B, the ratio of the amount of foaming agent A to the total amount of foaming agent A and foaming agent B is preferably in the range of 50 to 85%. If the ratio of the amount of foaming agent A to the total amount of foaming agent A and foaming agent B2 satisfies the above range, it is particularly preferable because it is easy to maintain a low thermal conductivity.

[0047] By setting the ratio of the amount of foaming agent A to the total amount of foaming agent A and foaming agent B (foaming agent B1 and / or foaming agent B2) within the above-mentioned range, it is possible to easily maintain low thermal conductivity and obtain a foamed board with excellent appearance.

[0048] In the present invention, by setting the blending amount of foaming agent A, the blending amount of foaming agent B, and the ratio of the blending amount of foaming agent A to the total blending amount of foaming agents A and B within the above-mentioned specific ranges, it is possible to obtain an extruded foam board that has excellent moldability (shapeability) and good appearance, even when a large amount of HFO is blended.

[0049] In addition, when foaming agent C is used together with foaming agent A and foaming agent B as the foaming agent, the amount of foaming agent C is preferably 0.3 to 0.7 mol per kg of base resin. Since foaming agent C is a foaming agent that dissipates quickly, it can improve the foaming property without deteriorating the thermal conductivity or flame retardancy. From this viewpoint, the amount of the foaming agent is more preferably 0.4 to 0.6 mol per kg of base resin.

[0050] According to the manufacturing method of the present invention, by using a specific ratio of a blowing agent A consisting of 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) and a blowing agent B containing at least one of a 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd) blowing agent B1 and a 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) blowing agent B2 as the physical blowing agent, it is possible to obtain an extruded polystyrene resin foam board having excellent long-term low thermal conductivity, excellent surface smoothness, few gas spots, and small shrinkage.

[0051] <Other ingredients> (Flame retardant) The foamed board obtained by the manufacturing method of the present invention is mainly used as a heat insulating material for building materials, and flame retardancy is imparted by blending a flame retardant with the base resin. The flame retardant used in the present invention is not particularly limited, but it is preferable to use a brominated flame retardant. Examples of the brominated flame retardant include brominated butadiene-based polymers such as brominated butadiene-styrene copolymers, tetrabromobisphenol-A-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-S-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-F-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-A-bis(2,3-dibromopropyl ether), tetrabromobisphenol-B-bis(2,3-dibromopropyl ether), tetrabromobisphenol-C-bis(2,3-dibromopropyl ether), tetrabromobisphenol-D ... Examples of the brominated bisphenol compounds are brominated bisphenol compounds such as tetrabromobisphenol-S-bis(2,3-dibromopropyl ether) and tetrabromobisphenol-F-bis(2,3-dibromopropyl ether), and brominated isocyanurates such as tris(2,3-dibromopropyl)isocyanurate, mono(2,3,4-tribromobutyl)isocyanurate, di(2,3,4-tribromobutyl)isocyanurate, and tris(2,3,4-tribromobutyl)isocyanurate. These brominated flame retardants can be used alone or in combination.

[0052] In addition to these bromine-based flame retardants, nitrogen-containing cyclic compounds such as cresyl di-2,6-xylenyl phosphate, antimony trioxide, diantimony pentoxide, ammonium sulfate, zinc stannate, cyanuric acid, pentabromotoluene, isocyanuric acid, triallyl isocyanurate, melamine cyanurate, melamine, melam, and melem; silicone-based compounds; inorganic compounds such as boron oxide, zinc borate, and zinc sulfide; and phosphorus-based compounds such as phosphate esters represented by triphenyl phosphate, red phosphorus, ammonium polyphosphate, phosphazene, and hypophosphites.

[0053] Among these flame retardants, it is more preferable to use a flame retardant that combines tetrabromobisphenol A bis(2,3-dibromopropyl ether) and tetrabromobisphenol A bis(2,3-dibromo-2-methylpropyl ether), or a flame retardant that contains a brominated butadiene-styrene copolymer, because these can impart high flame retardancy, are less likely to decompose the polystyrene resin during extrusion, and make it easy to stably obtain a foamed board even when the foamed board has a low apparent density (high expansion ratio) and a large cross-sectional area.

[0054] The amount of the flame retardant is preferably 0.1 to 10 parts by mass, more preferably 1 to 9 parts by mass, and even more preferably 1.5 to 7 parts by mass, relative to 100 parts by mass of the base resin, since the amount can impart high flame retardancy to the foam board and can suppress deterioration of extrusion foamability and mechanical properties. If the amount is within this range, the flame retardant does not inhibit foamability, and a foam board having high flame retardancy such as the flammability standard for extruded polystyrene foam insulation described in "Test Method A" specified in the flammability test method of JIS A9521:2017 can be obtained.

[0055] (Flame retardant assistant) In the method of the present invention, a flame retardant auxiliary can be used in combination with the flame retardant to further improve the flame retardancy of the foam board. Examples of the flame retardant auxiliary include one or more selected from diphenylalkanes and diphenylalkenes such as 2,3-dimethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 2,4-diphenyl-4-methyl-1-pentene, and 2,4-diphenyl-4-ethyl-1-pentene, and polyalkylated aromatic compounds such as poly-1,4-diisopropylbenzene. The amount of the flame retardant auxiliary is generally 0.01 to 1 part by mass, more preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the base resin.

[0056] (Radiation suppressant) In the manufacturing method of the present invention, graphite can be blended as a radiation suppressant in the foamable resin composition in order to improve the heat insulating property. Graphite can improve the heat insulating property of the foam board by reflecting infrared rays.

[0057] Examples of graphite include flake graphite, scaly graphite, artificial graphite, and earthy graphite, and it is preferable to use graphite whose main component is flake graphite. As described later, it is preferable to use graphite as a master batch in which the graphite is mixed at a high concentration with a polystyrene resin. Graphite having a fixed carbon content of 80% or more is preferable because it has good workability when producing a master batch and has an excellent effect of improving the heat insulation of the resulting foam board. In addition, in order to further improve the heat insulation of the foam board, graphite having a fixed carbon content of 90% or more is more preferable, and graphite having a fixed carbon content of 95% or more is even more preferable. The fixed carbon content of the graphite refers to a value measured by the method described in JIS M8511:2014.

[0058] The amount of graphite to be blended is preferably 0.2 to 10 parts by mass relative to 100 parts by mass of the base resin. When the amount is within this range, the heat insulating properties are improved, and a foam board having a desired low thermal conductivity can be obtained. From this viewpoint, the amount of graphite to be blended is more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, relative to 100 parts by mass of the base resin of the foam board. On the other hand, from the viewpoint of maintaining the flame retardancy of the foam board, the upper limit of the amount of graphite to be blended is more preferably 5 parts by mass, even more preferably 3 parts by mass, and particularly preferably 1 part by mass.

[0059] In addition, in the manufacturing method of the present invention, the foam board can contain a radiation suppressor other than the graphite in order to further improve the heat insulation. Examples of the radiation suppressor other than graphite include one or more selected from metal oxides such as titanium oxide, metals such as aluminum, ceramics, carbon black, graphite, infrared shielding pigments, hydrotalcite, etc. Among these, titanium oxide is preferably used. The amount of the radiation suppressor other than graphite to be added is about 0.5 to 5 parts by mass, more preferably 1 to 4 parts by mass, based on 100 parts by mass of the base resin.

[0060] In the method of the present invention, other known additives may be appropriately blended with the base resin as necessary, such as a cell regulator, a colorant such as a pigment or a dye, a heat stabilizer, a filler, and the like.

[0061] (Foam regulator) In the production method of the present invention, it is preferable to form the foamable resin composition by blending a cell control agent with the base resin. As the bubble regulator, inorganic powders such as talc, kaolin, mica, silica, calcium carbonate, barium sulfate, titanium oxide, clay, aluminum oxide, bentonite, and diatomaceous earth can be used. Among them, talc is preferred because it is easy to adjust the bubble diameter and to reduce the bubble diameter without impairing flame retardancy, and fine talc with a 50% particle size (light transmission centrifugal sedimentation method) of 0.1 to 20 μm is particularly preferred, and fine talc with a 50% particle size (light transmission centrifugal sedimentation method) of 0.5 to 15 μm is particularly preferred. The amount of the bubble regulator to be added varies depending on the type of regulator, the target bubble diameter, etc., but when talc is used as the bubble regulator, it is preferably 0.1 to 7 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass per 100 parts by mass of the base resin.

[0062] (Heat stabilizer) The thermal stabilizer can improve the thermal stability of the bromine-based flame retardant by blending it with raw materials or scraps when manufacturing a foam board or when recycling and repelletizing scraps of a foam board. Examples of the thermal stabilizer include one or more thermal stabilizers selected from bisphenol-type epoxy compounds and novolac-type epoxy compounds such as EPICLON series manufactured by DIC Corporation, hindered phenol compounds such as pentaerythritol tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate], and phosphite compounds such as bis (2,6-di-t-butyl-4-methylphenyl) pentaerythritol diphosphite. The blending amount of the thermal stabilizer is preferably 0.1 to 40 parts by mass with respect to 100 parts by mass of the total amount of the flame retardant.

[0063] In the manufacturing method of the present invention, as a method of blending the flame retardant and other additives into the base resin, a method of feeding a predetermined ratio of the flame retardant and other additives together with the base resin to a feed section provided upstream of the extruder and kneading them in the extruder can be adopted. In addition, a method of feeding the flame retardant and other additives into the molten resin from a feed section provided midway through the extruder can also be adopted. Specifically, a method of feeding a dry blend of the flame retardant, other additives, and base resin to the extruder and melt-kneading it, a method of feeding a molten kneaded product obtained by kneading the flame retardant, other additives, and base resin with a kneader or the like to the extruder, a method of preparing a master batch in which a high concentration of the flame retardant and other additives is blended in advance with the base resin, feeding this to the extruder and melt-kneading it with the base resin, and the like can be adopted. In particular, from the viewpoint of dispersibility, it is preferable to adopt a method of preparing a flame retardant master batch and feeding it to the extruder. The flame retardant masterbatch is prepared by using a polystyrene resin having an MFR of about 0.5 to 30 g / 10 min as the base resin, and adjusting the masterbatch so that the flame retardant content is 10 to 95 mass %, more preferably 30 to 90 mass %, and even more preferably 50 to 85 mass %.

[0064] <Physical properties of foam board> Next, the extruded polystyrene resin foam board obtained by the production method of the present invention will be described. (Cross-sectional area, dimensions, etc.) The foamed plate of the present invention is in the form of a plate, and its cross-sectional area perpendicular to the extrusion direction is 100 cm 2 More than 200cm 2 The upper limit of the cross-sectional area is approximately 1500 cm 2 In this specification, the cross-sectional area perpendicular to the extrusion direction refers to the area of ​​a cross section perpendicular to the extrusion direction of the foam board.

[0065] The foam board of the present invention is usually produced by preparing an original board having a size at least one size larger than the desired size, and then cutting the original board to adjust the width, length, and in some cases the thickness.

[0066] However, if the width of the original plate changes significantly during production and becomes narrower than the specified width, it becomes impossible to obtain a foamed board of the specified size, resulting in a poor yield. In addition, in the production of a foamed board, the smaller the apparent density and the larger the cross-sectional area, the more difficult it tends to be to foam. According to the production method of the present invention, even when a foamed board having a large thickness and cross-sectional area is produced, a foamed board with a good appearance can be stably produced. The extruded foamed board with a good foaming state and excellent surface smoothness can be suitably used as a foamed board with a molded skin without cutting the surface in the thickness direction.

[0067] In the case of a foam board used as a heat insulating material, its thickness is preferably 20 mm or more, more preferably 30 mm or more, and even more preferably 50 mm or more, while the upper limit of the thickness is preferably 150 mm, and more preferably 130 mm.

[0068] The width is preferably 800 mm or more, more preferably 900 mm or more, with the upper limit being approximately 1200 mm.

[0069] (Apparent density) The apparent density of the foamed board of the present invention is 20 to 50 kg / m 3 and preferably 30 to 40 kg / m 3When the apparent density is within the above range, the material has sufficient mechanical strength and is lightweight, making it suitable for use as a heat insulating material.

[0070] (Closed bubble rate) The closed cell ratio of the foam board is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. If the closed cell ratio is within this range, the foaming agent is likely to remain in the bubbles, and the high heat insulating performance of the foam board can be maintained for a long period of time. In addition, the foam board can have excellent mechanical strength such as compressive strength.

[0071] The closed cell ratio of the extruded foam board in this specification is measured according to procedure C of ASTM-D2856-70 using a Toshiba Beckman Co., Ltd. air comparison type specific gravity meter 930 (a cut sample without a molded skin cut into a size of 25 mm x 25 mm x 20 mm from the extruded foam board is placed in a sample cup and measured. However, if the thickness is too thin to cut a 20 mm cut sample in the thickness direction, for example, two cut samples of a size of 25 mm x 25 mm x 10 mm may be placed in the sample cup at the same time and measured.) using the true volume Vx of the extruded foam board (cut sample) and the closed cell ratio S (%) is calculated using the following formula (1), and the average value of N = 3 is obtained.

[0072] S(%)=(Vx-W / ρ)×100 / (V A -W / ρ) (1) Vx: The true volume (cm) of the cut sample measured by the above method 3 ) (This corresponds to the sum of the volume of the resin that constitutes the cut sample of the extruded foam board and the total volume of the air bubbles in the closed cell portion of the cut sample.) V A : Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total weight of cut sample used for measurement (g) ρ: Density of the resin that composes the extruded foam board (g / cm 3 )

[0073] (Bubble structure: average bubble diameter in thickness direction) The average cell diameter in the thickness direction of the foam board is preferably 50 to 200 μm, more preferably 70 to 170 μm, and even more preferably 80 to 150 μm. When the average cell diameter is within the above range, the thermoplastic resin foam board has higher heat insulation properties and superior mechanical strength.

[0074] The method for measuring the average bubble diameter in the thickness direction is as follows: The average bubble diameter in the thickness direction is determined by taking enlarged photographs at three locations, namely, the center and both ends of a cross section perpendicular to the width direction of a foamed board, adjusting the magnification to a range of about 50 to 200 times so that the number of cells in the photograph is about 200 to 500, measuring the maximum diameter of each bubble in the thickness direction on each photograph using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and calculating the arithmetic average of these values.

[0075] (Bubble structure: bubble deformation rate) Further, in the thermoplastic resin foam board, the bubble deformation ratio is preferably 0.7 to 1.5. The bubble deformation ratio is a value calculated by measuring the maximum diameter of each bubble in the width direction of an enlarged photograph of bubbles using image processing software NS2K-pro manufactured by Nano System Co., Ltd., in the same manner as the average bubble diameter in the thickness direction, and dividing the average bubble diameter in the thickness direction by the average bubble diameter in the width direction, and the smaller the bubble deformation ratio is than 1, the flatter the bubbles are, and the larger the bubble deformation ratio is than 1, the longer the bubbles are. When the bubble deformation ratio is within the above range, the thermoplastic resin foam board has excellent mechanical strength and higher thermal insulation. The lower limit of the bubble deformation ratio is more preferably 0.8 from the viewpoint of the compressive strength and dimensional stability of the foam board. Moreover, the upper limit of the bubble deformation ratio is more preferably 1.1, and even more preferably 1.05, from the viewpoint of the effect of improving thermal insulation.

[0076] (Thermal conductivity after 7 days) In the foam board of the present invention, the thermal conductivity 7 days after production is preferably 0.025 W / m·K or less, more preferably 0.024 W / m·K or less, and even more preferably 0.023 W / m·K or less.

[0077] (Thermal conductivity after 100 days) Furthermore, the thermal conductivity 100 days after production is preferably 0.027 W / m·K or less, more preferably 0.026 W / m·K or less, and even more preferably 0.025 W / m·K or less.

[0078] The thermal conductivity can be measured based on the heat flow meter method described in JIS A1412-2:1999 (one test piece, symmetrical configuration, high temperature side 38° C., low temperature side 8° C., average temperature 23° C.). EXAMPLES

[0079] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0080] In the examples and comparative examples, the following devices and raw materials were used.

[0081] The extrusion device used was a 1st extruder of a high mixing type with an inner diameter of 115 mm and a 2nd extruder with an inner diameter of 180 mm connected in series, a physical foaming agent injection port was provided near the end of the 1st extruder, and a flat die equipped with a resin discharge port (die lip) with a rectangular cross section with a gap of 1 mm and a width of 440 mm was connected to the outlet of the 2nd extruder. In addition, a molding device (guider) consisting of a pair of upper and lower plates made of polytetrafluoroethylene resin, which were horizontally installed at a substantially constant interval, was attached to the resin outlet of the 2nd extruder.

[0082] (1) Base resin (1-1) Polystyrene resin: DIC Corporation polystyrene "HP780AN", melt viscosity (200℃, 100sec -1 )1900 Pa·s (1-2) Polyester resin: spiroglycol modified polyethylene terephthalate "ALTESTER3012" manufactured by Mitsubishi Gas Chemical Co., Inc., terephthalic acid 100% by mass, spiroglycol / ethylene glycol = 30% by mass / 70% by mass, melt viscosity 2000 Pa s The melt viscosity was measured using a Capillograph 1D (manufactured by Toyo Seiki Seisakusho Co., Ltd.) flow characteristic measuring device at a temperature of 200°C and a shear rate of 100 sec -1 The values ​​were measured under the following conditions.

[0083] (2) Flame retardants (2-1) A flame retardant master batch (GR-134BG manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) containing a mixed flame retardant of 60% by mass of tetrabromobisphenol A bis (2,3-dibromo-2-methylpropyl ether): Dai-ichi Kogyo Seiyaku's "SR-130" / 40% by mass of tetrabromobisphenol A bis (2,3-dibromopropyl ether): Dai-ichi Kogyo Seiyaku's "SR-720" was used, and the master batch was added so as to obtain the amount of flame retardant shown in the table. (2-2) Brominated butadiene-styrene copolymer: A flame retardant masterbatch containing Emerald Innovation 3000 (E3000) flame retardant manufactured by LANXESS was used, and the masterbatch was added so as to obtain the amount of flame retardant shown in the table.

[0084] (3) Foam regulator Talc (manufactured by Matsumura Sangyo Co., Ltd., product name "High Filler #12", particle size (d50) 7.5 μm)

[0085] (4) Radiation suppressants (4-1) Graphite (Graphite: manufactured by Resino Color Kogyo Co., Ltd., product name: SBF-T-1683, flake graphite powder, average particle size 17 μm, 40% master batch) (4-2) Titanium oxide (manufactured by Nikko Bix Co., Ltd.)

[0086] (5) Physical foaming agents (A) 1,1,1,4,4,4-Hexafluoro-2-butene (HFO-1336mzz): manufactured by Mitsui Chemours Fluoroproducts (B1) 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd): manufactured by AGC (B2) 1-chloro-3,3,3-trifluoropropene (HFO-1233zd): manufactured by Honeywell Japan (C-1) Isobutane (C-2) 1,3,3,3-Tetrafluoropropene (HFO-1234ze): Honeywell Japan (C-3) Water (C-4) Ethanol: Yamaichi Chemical Industry Co., Ltd.

[0087] Examples 1 to 12, Comparative Examples 1 to 7 The types and amounts of base resin, flame retardant master batch, and cell regulator shown in Table 1 (Examples 1 to 12) and Table 2 (Comparative Examples 1 to 7) below were fed to a first extruder, heated to 200°C, and kneaded. The types and amounts of physical foaming agents shown in Tables 1 and 2 were fed from a physical foaming agent inlet provided in the first extruder, and further kneaded to form a foamable resin melt. Next, the resulting foamable resin melt was transferred to a second extruder to adjust the resin temperature, and then extruded into a guider at a discharge rate of 400 kg / hr. The foamed resin was passed through the guider while foaming to form (shape) a plate-like shape to produce a base plate of a foam plate thickness of 30 mm. Furthermore, the width and length of the base plate were adjusted by cutting, and the molded skins on both sides were evenly cut to produce a rectangular parallelepiped polystyrene resin foam plate (width: 910 mm, length: 1820 mm, thickness: 25 mm, cross-sectional area perpendicular to the extrusion direction: 227.5 cm) without a molded skin. 2 ) was manufactured.

[0088] [Table 1]

[0089] [Table 2]

[0090] For the foamed boards obtained in the Examples and Comparative Examples, the apparent density, closed cell ratio, cell structure (average cell diameter in the thickness direction, cell deformation rate), and thermal conductivity (after 7 days and 100 days) were measured by the following methods, and the flammability and appearance (surface smoothness, gas spots, and shrinkage) were evaluated according to the following criteria. The results are shown in Tables 1 and 2.

[0091] (Apparent density) The apparent density of the foam board was determined by the following method: A rectangular parallelepiped sample of 50 mm length × 50 mm width × 20 mm thickness was cut from the position where the obtained foam board was divided into two equal parts in the length direction and from the center and both ends in the width direction of the obtained foam board, and the mass was measured and the apparent density of each sample was determined by dividing the mass by the volume, and the arithmetic average of the masses was regarded as the apparent density.

[0092] (Closed bubble rate) The closed cell ratio of the foam board was calculated from the true volume Vx of the foam board measured using an air comparison type specific gravity meter (Toshiba Beckman Co., Ltd., air comparison type specific gravity meter, model: 930) according to procedure C of ASTM-D2856-70, using the following formula (1).

[0093] Bubble structure (average bubble diameter in thickness direction) The average bubble diameter in the thickness direction was determined as follows: Enlarged photographs were taken at a magnification of 100 times at three locations, namely, the center and both ends of the cross section perpendicular to the width direction of the foamed plate, where the foamed plate was divided into two equal parts in the length direction, and the maximum diameter of each bubble in the thickness direction was measured on each photograph using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and the average diameter was calculated by arithmetic mean.

[0094] Bubble structure (bubble deformation rate) The bubble deformation ratio was determined in the same manner as in the method for measuring the thickness direction bubble diameter described above. For an enlarged photograph of the bubbles, the maximum diameter of each bubble in the width direction was measured using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and the average bubble diameter in the width direction was calculated by arithmetically averaging these values, and then the average bubble diameter in the thickness direction was divided by the average bubble diameter in the width direction.

[0095] Specifically, cut samples were cut from the obtained foam board at a position that divided the foam board into two equal parts in the length direction, and at three positions near the center and both ends in the width direction of the foam board, and each cut sample was used as a measurement sample, and the closed cell ratio of each measurement sample was measured to determine the arithmetic average value of the closed cell ratio at the three positions. The cut samples used were cut from the foam board to a size of 25 mm length x 25 mm width x 20 mm thickness.

[0096] S(%)=(Vx-W / ρ)×100 / (Va-W / ρ) (1) In the formula, Vx, Va, W, and ρ are as follows: Vx: The true volume (cm) of the cut sample obtained by measurement using the air comparison type specific gravity meter 3 ) (This corresponds to the sum of the volume of the resin that constitutes the cut sample of the foam board and the total volume of the air bubbles in the closed cell part of the cut sample.) Va: Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total mass of cut samples used for measurement (g) ρ: density of the resin composition constituting the foam board (g / cm 3 )

[0097] (Thermal conductivity 7 days after manufacture) Test pieces measuring 200 mm in length, 200 mm in width, and 20 mm in thickness were cut out from the center of the width of the foamed board immediately after production, and the test pieces were stored in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50%. 7 days and 100 days after production, the thermal conductivity of each test piece was measured based on the flat plate heat flow meter method described in JIS A1412-2 (1999) (two heat flow meter method, high temperature side 38°C, low temperature side 8°C, average temperature 23°C).

[0098] (Thermal conductivity after 100 days of manufacture) The thermal conductivity after 100 days of manufacture is a value obtained by measuring the thermal conductivity of an extruded foam board subjected to test method A of the long-term change acceleration test of thermal resistance in accordance with JIS A1486:2014. Specifically, a rectangular parallelepiped of 200 mm long x 200 mm wide x 25 mm thick was cut out from the center of the width direction of the extruded foam board immediately after manufacture, and then a test piece of 200 mm long x 200 mm wide x 10 mm thick was cut out by evenly cutting it from both sides, and stored in a constant temperature and humidity room at a temperature of 23 ° C and a relative humidity of 50%, and the thermal conductivity was measured using the test piece 16 days after manufacture (corresponding to 100 days after manufacture of a 25 mm thick extruded foam board) based on the flat plate heat flow meter method (two heat flow meter method, high temperature side 38 ° C, low temperature side 8 ° C, average temperature 23 ° C) described in JIS A1412-2 (1999).

[0099] (flammability) Immediately after production, the foam board was stored in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50%. Four weeks after production, five test pieces (N=5) were randomly cut out from the foam board. The flammability was measured based on "Test Method A" specified in the flammability test method of JIS A9521:2017, and the flame retardancy of the foam board was evaluated according to the following criteria. Evaluation criteria ○: Disappears within 3 seconds for all five test pieces ×: The average burning time of the five test pieces exceeds 3 seconds (not applicable)

[0100] (Surface smoothness) The surface smoothness of the original plate and the extruded foam plate was visually evaluated according to the following criteria. ◎: The surfaces of the base plate and extruded foam plate are extremely good. ○: The surface of the base plate is rarely rough, but the surface of the extruded foam plate is extremely good. △: Roughness rarely occurs on the surface of the extruded foam board. ×: Many rough spots are observed on the surface of the extruded foam board.

[0101] (Gas Spot) Gas spots (excessively large bubbles observed on the surface and cross section of the foam plate due to separation of the foaming agent generated during extrusion foaming) were evaluated according to the following criteria. ◎: No spot holes were found on the original plate or extruded foam plate. ○: Almost no spot holes were observed in the original plate, and no spot holes were observed in the extruded foam plate. △: Spot holes are observed in some parts of the extruded foam plate. ×: Multiple spot holes were observed in the extruded foam plate, and a good foam plate was not obtained.

[0102] (Contraction) Shrinkage was evaluated by measuring the dimensional change by comparing the thickness of the foam board immediately after production with the thickness of the foam board 7 days after production, according to the following criteria. The foam board 7 days after production was measured at 23°C and 50% relative humidity after production. The thickness was measured at the center of the foam board, which is the position that divides the foam board into two equal parts in the length direction and width direction. The dimensional change was calculated from the following formula. [(Thickness of foam board immediately after manufacturing) - (Thickness of foam board 7 days after manufacturing)] x 100 ◎: Thickness dimensional change is less than 1% ○: Thickness dimensional change is 1% or more and less than 5% ×: Thickness dimensional change is 5% or more (not applicable)

[0103] From the results of each of the above measurements and evaluations, Examples 1 to 12, in which 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) (blowing agent A) and either 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd) (blowing agent B1) or 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) (blowing agent B2) were used as the physical blowing agent under the conditions of the present invention, showed good apparent density, cell structure, and thermal conductivity after 7 days and 100 days, and also showed good flammability and appearance.

[0104] In contrast, Comparative Examples 1 to 7, in which no foaming agent was used under the conditions of the present invention, all had inferior thermal conductivity after 7 days and 100 days compared to Examples 1 to 12.

[0105] Furthermore, molding itself was difficult in Comparative Example 3, in which 1,3,3,3-tetrafluoropropene (HFO-1234ze) (blowing agent A) and another HFO (HFO-1234ze) were used in combination as HFOs. Molding itself was difficult in Comparative Example 6, in which 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) (blowing agent A) and 1-chloro-2,3,3,3-tetrafluoropropene (HFO-1224yd) (blowing agent B1) were used in combination and the total amount of blowing agent A and blowing agent B was too small. In Comparative Example 7, in which 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) (blowing agent A) and 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) (blowing agent B2) were used in combination and the total amount of blowing agent A and blowing agent B was too small, molding itself was difficult.

Claims

1. The foaming method includes a step of extruding a foamable resin composition obtained by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and forming the composition into a plate shape using a molding tool. 3 , cross-sectional area perpendicular to the extrusion direction 100 cm 2 The above-mentioned method for producing an extruded polystyrene foam board comprises the steps of: The physical blowing agent is a blowing agent A consisting of 1,1,1,4,4,4-hexafluoro-2-butene; and a blowing agent B consisting of 1-chloro-2,3,3,3-tetrafluoropropene and / or 1-chloro-3,3,3-trifluoropropene; the total amount of the physical foaming agent is 1 to 1.5 mol per kg of the base resin; The amount of the foaming agent A blended is 0.2 to 0.7 mol per 1 kg of the base resin, The amount of the foaming agent B is 0.05 to 0.6 mol per 1 kg of the base resin, the total amount of the foaming agent A and the foaming agent B is 0.6 to 1.3 mol per kg of the base resin, A method for producing a polystyrene-based resin extruded foam board, characterized in that the ratio of the amount of foaming agent A (mol / kg) to the total amount of foaming agent A (mol / kg) and the amount of foaming agent B (mol / kg) is 30 to 90% (wherein the total amount of foaming agent A and the amount of foaming agent B is 100%).

2. 2. The method for producing a polystyrene-based resin extruded foam board according to claim 1, wherein the ratio of the total amount (mol / kg) of the foaming agent A and the total amount (mol / kg) of the foaming agent B to the total amount (mol / kg) of the physical foaming agents is more than 50% and not more than 80%.

3. The method for producing a polystyrene-based resin extrusion foam plate according to claim 1 or 2, characterized in that the ratio of the amount of foaming agent A (mol / kg) to the total amount of foaming agent A and the total amount of foaming agent B (mol / kg) is 50-85% (wherein the total amount of foaming agent A and the total amount of foaming agent B is 100%).

4. The method for producing a polystyrene-based resin extruded foam plate according to any one of claims 1 to 3, characterized in that the physical foaming agent comprises one or more foaming agents C selected from water, carbon dioxide, dialkyl ethers having 1 to 3 carbon atoms in the alkyl chain, and aliphatic alcohols having 1 to 5 carbon atoms, and the amount of the foaming agent C is 0.3 to 0.7 mol per 1 kg of the base resin.

5. 5. The method for producing an extruded polystyrene foam board according to claim 1, wherein the foaming agent A is mixed in an amount of 0.4 to 0.7 mol per 1 kg of the base resin.

Citation Information

Patent Citations

  • High-quality polymer foams from fluorinated alkene blowing agents

    JP2010522808A

  • Compositions and uses of cis-1,1,1,4,4,4-hexafluoro-2-butene

    JP2017141457A

  • Z-HFO-1336mzz blowing agent for foaming thermoplastic polymers, including polystyrene

    JP2019515112A

  • Fluorinated compounds useful as foam blowing agents - Patent Application 20070122997

    JP2020521009A

  • Compositions and uses of Z-1-chloro-2,3,3,3-tetrafluoroprop-1-ene

    JP2020531633A